2015
DOI: 10.5152/dir.2015.14403
|View full text |Cite
|
Sign up to set email alerts
|

The role of computed tomography in the diagnosis of acute and chronic pulmonary embolism

Abstract: A cute pulmonary embolism (PE) is the third most common cardiovascular condition, after coronary artery disease and stroke (1). Due to lack of specific sets of symptoms that accurately predict or exclude the diagnosis of acute PE, the diagnosis strongly relies on noninvasive imaging techniques. Diagnostic strategies for evaluating PE have undergone important changes over the past decades (2). Due to rapid technical advances in speed and spatial resolution, the utility of computed tomography (CT) angiography ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 110 publications
2
60
0
Order By: Relevance
“…These findings within Table 1 correlate to the review by Doğan et al [15] where the variation in sensitivity and specificity for radiologist diagnosis of PE was reviewed and respectively re- MDCT: multi-detector CT ported as ranging from 83-100%, and from 89-96%, again with the exception of 68-100% sensitivity reported by Wittenberg et al [13]. The study by Wittenberg et al [13] also further reported on individual reporting radiologist's sensitivity and specificity for diagnosis of patients with PE, and can account for the greater range in sensitivity (68-100%) reported in their study, where one particular radiologist had a lower diagnostic sensitivity of 68%.…”
Section: Diagnostic Accuracy Of Ctpa With Radiologist Interpretationsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings within Table 1 correlate to the review by Doğan et al [15] where the variation in sensitivity and specificity for radiologist diagnosis of PE was reviewed and respectively re- MDCT: multi-detector CT ported as ranging from 83-100%, and from 89-96%, again with the exception of 68-100% sensitivity reported by Wittenberg et al [13]. The study by Wittenberg et al [13] also further reported on individual reporting radiologist's sensitivity and specificity for diagnosis of patients with PE, and can account for the greater range in sensitivity (68-100%) reported in their study, where one particular radiologist had a lower diagnostic sensitivity of 68%.…”
Section: Diagnostic Accuracy Of Ctpa With Radiologist Interpretationsupporting
confidence: 88%
“…Worldwide acceptance of CTPA as a gold standard diagnostic tool for PE has been achieved following the PIOPED II study and reviews like that published by Doğan et al [15]. Although a high sensitivity for PE diagnosis has been established, there is still a false negative proportion of 13% as per the PIOPED II results, and this could lead to significant negative health outcomes.…”
Section: Diagnostic Accuracy Of Ctpa With Radiologist Interpretationmentioning
confidence: 99%
“…Dogan et al analyzed the role of CT in the diagnosis of acute and chronic PE. 9 International multicenter echocardiographic are comparable for predicting 30-day mortality. [14][15][16][17][18] These results were consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the clinical role of CTPA examination has undergone extensive scientific investigations [7][8][9][10]. The largest and most significant collaborative clinical trial was conducted in 2006 [10].…”
Section: Ctpa's Sensitivity Specificity and Negative And Positive Pmentioning
confidence: 99%
“…On the other hand, based on the PE location is lobar, segmental, or subsegmental vessels, the PPV was 97, 68, and 25%, respectively. The defects at extreme sites of pulmonary vascular branches (segmental and subsegmental vessels) exhibit less observability, and consequently more challenging to radiologists, than lobar and main PA clots.A recent report, in 2015, was published by Dogan et al in the Netherlands; this study reviewed different CTPA clinical trials and reported that the sensitivity and specificity of CTPA scans may vary between the range of 83-100% and 89-96%, respectively[8]. The NPV was 96-99% showing the high CTPA scan's certainty in ruling out PE; a negative CTPA can safely exclude PE.…”
mentioning
confidence: 97%